Study of the Properties of Concrete Based on Non-Fired Alkaline Binders - A. I. Khamidov; S. Khakimov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article deals with the use of film-forming materials for the care of freshly laid concrete based on non-firing alkaline binders, the results of studies to determine the strength, frost resistance and plastic shrinkage of concrete are presented.